Training model with body composition and physical fitness tests for 12-15 year old ski jumpers - Rybakova, E. O.; Shutova, T. N.; Vozisova, M. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test benefits of a new gender-specific training model for the 12-15 year old ski jumpers with the body composition tests and physical fitness tests.